The Psychometric Score for Hepatic Encephalopathy and the Stroop EncephalApp in the diagnosis of covert hepatic encephalopathy in Cuba - Padilla Ruiz, Maykel Alain (2021)
Introduction: The early diagnosis of occult hepatic encephalopathy in patients with liver cirrhosis is currently a challenge, mainly with regard to diagnostic tests. Objetive: The aim of this study was to compare the results of two tests, the psychometric score for hepatic encephalopathy and the Stroop EncephalApp in the diagnosis of covert hepatic encephalopathy. Materials and methods: The two tests were applied in patients in the cirrhosis consultation of the "Arnaldo Milián" Hospital in Villa Clara, comparing the results of Stroop EncephalApp taking as reference the psychometric score for hepatic encephalopathy. The variables age, sex and schooling were adjusted according to population norms. Results: A total of 80 cirrhotic patients were included, as well as 520 healthy controls. Using the Stroop EncephalApp, 35% presented covert hepatic encephalopathy, when the Psychometric score for hepatic encephalopathy was used. The prevalence was 40%, showing the sensitivity of Stroop EncephalApp of 80% and 82% of specificity. Conclusions: undiagnosed occult hepatic encephalopathy shows a high prevalence in cirrhosis. The psychometric score for hepatic encephalopathy and Stroop EncephalApp show adequate sensitivity in the diagnosis of occult hepatic encephalopathy.